(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study investigated entrepreneurs’ ratings of finance operational strategies needed for improving the performance of small and medium enterprises in Delta State. A research questions guided the study while null hypotheses was formulated. The descriptive survey research design was adopted for the study. The study was conducted in Delta State. The population for this study consisted of 1,310 registered small and medium scale enterprises with the Delta State Ministry of Trade, Investment, Commerce and Industry. A sample of 393 entrepreneurs of small and medium scale enterprises in Delta State was used for the study using proportionate stratified sampling technique. The instrument used for data collection was a 40-item questionnaire, which was validated by three experts. The instrument was subjected to test of internal consistency using Cronbach’s alpha method, and a coefficient of 0.83 was obtained. Mean and standard deviation was used to answer the research questions while analysis of variance was used to test the null hypotheses at 0.05 alpha level. The findings revealed that entrepreneurs rate finance operational strategies as greatly needed for improving the performance of SMEs in Delta State. The finding also revealed that there was a significant difference in the mean ratings of entrepreneurs on finance operational strategy needed for improving performance of SMEs based on their years of experience. Based on the findings, it was recommended amongst others that the Department of Small and Medium Scale Enterprises with Delta State Ministry of Trade, Investment, Commerce and Industry should set up personnels to check up the financial internal control system of small and medium enterprises.